Leptin and hypertension in obesity - Paco E Bravo; Stephen Morse; David M Borne; Erwin A Aguilar; Efrain Reisin (Vascular Health and Risk Management, 2006)
Paco E Bravo1, Stephen Morse1, David M Borne2, Erwin A Aguilar1, Efrain Reisin11Sections of Nephrology and 2Comprehensive Medicine, Department of Internal Medicine, Louisiana State University Health Sciences Center, New Orleans, LA, USAAbstract: Leptin, a peptide discovered more than 10 years ago, decreases food intake and increases sympathetic nerve activity to both thermogenic and nonthermogenic tissue. Leptin was initially believed to be an anti-obesity hormone, owing to its metabolic effects. However, obese individuals, for unknown reasons, become resistant to the satiety and weight-reducing effect of the hormone, but preserve leptin-mediated sympathetic activation to nonthermogenic tissue such as kidney, heart, and adrenal glands. Leptin has been shown to influence nitric oxide production and natriuresis, and along with chronic sympathetic activation, especially to the kidney, it may lead to sodium retention, systemic vasoconstriction, and blood pressure elevation. Consequently, leptin is currently considered to play an important role in the development of hypertension in obesity.Keywords: leptin, renal sympathetic nerve activity, blood pressure, obesity, selective leptin resistance, nitric oxide, natriuresis